Exploring the Influence of Student Affairs on Adjustment and Adaptation for Indonesian Graduate Students - Nguyen, David J.; Larson, Jay B. (Journal of International Students, 2017)
This qualitative study explored the influence of student affairs on academic adjustment and adaptation for 10 Indonesian graduate students at a single campus. Semi-structured interviews explored student affairs’ role in adaptation and transition to collegiate life in the United States. Analyses illuminated ways in which participants experienced disequilibrium attending U.S. institutions arising from pre-arrival constructed images of college life in the United States. Student affairs functional areas disrupted these stereotypes for students and devised strategies for Indonesian students to feel more welcomed and included. Study participants described the importance of culturally-relevant student organizations, inclusive environments, and religiously affiliated centers in their adjustment. The article concludes with practical implications for student affairs professionals and higher education institutions.